Makna Perkataan Paulus “Menggenapkan dalam Dagingku Apa yang Kurang pada Penderitaan Kristus” menurut Kolose 1:24 - Reniati Esri Nabunome; Lea Adelia Dael; Malik Bambangan (Pusat Riset dan Inovasi Nasional, 2025)
Suffering is a condition where a person experiences pain or difficulty in living their life. Paul's words about